Performance Dashboard Sebagai Visualisasi Evaluasi Diri Perguruan Tinggi Menggunakan Pendekatan User-Centric - Adam Bachtiar Maulachela; Jihadil Qudsi; Abdurahim Abdurahim; Muhammad Tajuddin (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
The Government of Indonesia, through the Ministry of Education and Culture, mandates each university to organize quality education. To produce graduates who meet national standards of higher education (SN-Dikti). Hence, each university must evaluate its performance to know its current condition. Unfortunately, most universities in Indonesia have difficulty in measuring their performance. Therefore, the university becomes difficult to establish a strategic plan forward. This study aims to produce a performance dashboard that can help university leaders evaluate their performance. This Performance Dashboard visualizes Key Performance Indicator (KPI) information from a strategic plan in one screen. This research uses a user-centric approach with four main stages, namely, identification of needs, planning, prototype design, and prototype review to produce the performance dashboard. The Performance Dashboard produces interactive gauge charts (baseline, targets, and performance achievements) so that it can visualize university KPI information. The results of user reviews showed that the KPI visualization by the performance dashboard was declared correct and could be useful as a guide in preparing a self-evaluation.